Local and Intra-articular Administration of Nonsteroidal Anti-inflammatory Drugs for Pain Management in Orthopedic Surgery. (10th March 2022) - Bernthal, Nicholas M.; Hart, Christopher M.; Sheth, Ketan R.; Bergese, Sergio D.; Ho, Hung S.; Apfel, Christian C.; Stoicea, Nicoleta; Rojhani, Allen; Jahr, Jonathan S.
Abstract : Background: Although growing evidence demonstrates the benefits of locally administered nonsteroidal anti-inflammatory drugs (NSAIDs) for postoperative pain management, there is ongoing debate regarding NSAID use in orthopedic surgery. Areas of Uncertainty: Current data largely support a local site of NSAID action and suggest that effective pain control can be achieved with delivery of NSAIDs intra-articularly (IA) and/or locally at the site of injury, where they can block peripheral production of inflammatory mediators and may desensitize nociceptors. Improvements in postoperative pain control with locally administered NSAIDs have been widely reported in the total joint arthroplasty literature and may offer benefits in patient's undergoing arthroscopic procedures and those with osteoarthritis as well. The purpose of this review is to examine the available evidence in the literature regarding the efficacy and safety profile of the use of local and IA NSAIDs in orthopedic surgery. Data Sources: Narrative literature review using keywords, expert opinion, either during or from live conference. Therapeutic Advances: Local and IA administration of NSAIDs for pain management in orthopedic surgery. Conclusion: There is convincing evidence that NSAIDs administered locally in and around the joint reduce postoperative pain scores and opioid consumption in patients undergoing total joint arthroplasty, yet further research is required regarding the risks of potential chondrotoxicity and the inhibition of bone and soft-tissue healing with locally administered NSAIDs.